Polysaccharides based materials as active packaging for food applications: A review - Kusuma Isnainul; Rahmadhia Safinta Nurindra; Ma’arif Alfian (BIO Web of Conferences)
In the food sector, one way to support the achievement of the SDGs goals responsible consumption and production is to implement edible or biodegradable food packaging. Food packaging has the main function of protecting food items. Based polysaccharides are one source of material that used to food packaging. Materials of polysaccharide based such as cellulose, hemicellulose, pectin, chitin, starch, and alginate. Polysaccharide based packaging has the potential to be used as active packaging with the addition of active ingredients which can increase the shelf life of the product. Polysaccharides have great potential to be used as active packaging materials for food. Polysaccharides as active packaging materials play an active role in the quality and durability of food either by acting as scavengers or inactivating harmful compounds through the release of desired components, which have antimicrobial or antioxidant properties. However, further research is needed to optimize their performance and overcome production and processing issues to facilitate their commercialization.